TI_GERICHTE 52.2019.621 vom 6. November 2019 , Istanza di restituzione del termine di ricorso dinanzi al Consiglio di Stato - TI Tribunale d'appello (2019)
Istanza di restituzione del termine di ricorso dinanzi al Consiglio di Stato